Financial accountability: organizational performance improvement through culture control and contractibility - Muttaqin, Galih Fajar; Mulyasari, Windu (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2018)
This study focuses on performance contracts and the use of performance measurement systems that can affect the performance of government organizations. Implementation of the Contract / Performance Agreement was only implemented in 2015, so it is worth investigating. The context of this research becomes very important to see the reality that occurs in government agencies that tend to report excessive good performance and minimize information about the failure of the program. Performance reports submitted in the form of Government Institution Performance Accountability Report (LAKIP) have been biased. The bias arises because the performance that is delivered is not like the reality in the field so as to mislead the public as the information user and ultimately result in excessive expectations of government institutions. This study examines the influence of contractibility and culture control on the organization's performance and financial accountability of the Regional Government Agency of Banten Province using SEM-PLS test equipment. Test results of 145 sampled data that spread throughout the district in Banten Province resulted in the conclusion (1) contractibility positively affects the performance of public sector organizations; (2) culture control positively affects the performance of public sector organizations; (3) the performance of the organization positively affects the financial accountability of public sector organizations